A Mixed-Methods Evaluation of the Implementation of a Performance Measurement System for South Africa's Substance Use Treatment Services - Myers-Franchi, Bronwyn; Williams, P.P.; Govender, R.; Manderscheid, R.; Koch, J.R. (ALCOHOL RES DOCUMENTATION INC CENT ALCOHOL STUD RUTGERS UNIV, 2019)
OBJECTIVE: Minimal knowledge exists on the factors that affect implementation of performance measurement systems, particularly in low- and middle-income countries (LMICs). To address this, we describe the implementation of a performance measurement system for South Africa's substance abuse treatment services known as the Service Quality Measures (SQM) initiative.